Elongating modified conserved peptides eliminates their immunogenicity and protective efficacy against P. falciparum malaria (2005)
Plasmodium falciparum malaria protein peptides were synthesised in the search for more effective routes for inducing a protective immune response against this deadly parasite and this information has been associated with such molecules’ three-dimensional structure. These peptides had high red blood cell binding activity and their carboxy- and amino-terminal extremes were elongated for determining their immunogenic and protection-inducing activity against this disease in the Aotus monkey experimental model. 1H-NMR was used for analysing their three-dimensional structure; FAST ELISA, immunofluorescence antibody test, and Western blot were used for identifying their antibody inducing capacity and these previously immunised Aotus were inoculated with a highly infective P. falciparum strain to determine whether these elongated peptides were able to induce protection. This was aimed at establishing an association or correlation between long peptides’ three-dimensional structure and their immunogenic and protection-inducing response in these monkeys. Peptides 20026 (25 residue), 20028 (30 residue), and 20030 (35 residues) were synthesised based on elongating the amino-terminal region of the 10022 highly immunogenic and protection-inducing modified peptide. 1H-NMR studies revealed that the first three had Classical type III ?-turn structures, different from the 20-amino acid long modified peptide 10022 which had a distorted type III ?-turn. Humoral immune response analysis showed that even when some antibodies could be generated against the parasite, none of the immunised Aotus could be protected with elongated peptides suggesting that elongating them eliminated modified peptide 10022 immunogenic and protection-inducing capacity.